Republic of Armenia : Third Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2003)
This paper evaluates the Republic of Armenia's Third Review Under the Poverty Reduction and Growth Facility (PRGF) and a Request for Waiver of Performance Criterion. The PRGF-supported program remains on track. All but one of the December 2002 quantitative performance criteria were met, and all structural measures envisaged for implementation up until February 2003 have been carried out or implemented as a prior action for the third review. The targets on tax revenue, stock of domestic arrears, fiscal deficit, and net international reserves were met with comfortable margins.